Stress control practices for mental balance improvement in academic sports - Shcherbakova, O. I.; Chernykh, A. K.; Balakhanova, D. A.; Midova, O. V. (Theory and Practice of Physical Culture, 2018)
The study gives a special priority to the still underexplored issues of stress tolerance and stressors in the modern academic sports in the context of the relevant psychological theory and practices, for the mental conditioning purposes. It is common knowledge today that the stress test, prevention and mitigation issues are critically important for success in sports on the whole and emotionally intensive sport disciplines in particular with their stressful interpersonal communication environments. A special priority shall be given to the early stress detecting tests with a variety of stress test methods and tools to rate individual stress exposures and apply, on a timely basis, the most efficient stress mitigation, control and tolerance building policies and practices. Subject to the stress typing and rating tests under the study was a group of academic athletes, with tests of a stress control model of the authors` own design including the special stress control and mitigation practices to efficiently build up the individual stress tolerance.